Домашняя юридическая энциклопедия. Семья: энциклопедия / Ред. И.М. Кузнецова - Кузнецова И.М. (Олимп, 1997)
Экземпляры: ф. 12 (20210827) / Инвентарный номер: 29367 / Цена: 36.00 / Сис.шифр: 67.624я20 / Авт.знак: Д66 / ГРНТИ: 10.47 / ББК: 67.624 я20